DINAMIKA SOSIO-KULTURAL KEAGAMAAN MASYARAKAT MADURA(Kiprah dan Eksistensi Khodam Dalam Pesantren di Madura) - Supandi, Supandi (Universitas Islam Madura, 2017)
The meaning and function khodam in boarding schools at essence is another name of the aide, although no terms khoddam is similar with supernatural powers that not everyone can see, feel and communicate, the meaning of khoddam is also as students that in addition look for a knowledge, they also help caregiver in implementing the tasks of boarding school uniquely and home domesticity, in order to achieve a goal, which is to get a blessing from acaregiver or teachers, although some khoddams that of the elements of an outsider who are never become Islamic students , khoddam is one alternative for students who want to study at the school but does not have enough money to live, so to be khoddam, then they can get an education with the assistance of the cost of education has been given bycaregiver . The view of the existence of khodam basically, they were petrified in successful educational process, with their presence, the students, religious and even the general public is easier to communicate with the caregiver, he lookedatkhoddam as students are in imaginably, otherwise, khoddam already considered as part of a large family of schools so that there is no difference between regular students with students who concurrently becomes khoddam.